Special silicone rubber for cold shrinkable cable terminal accessories and its preparation method
Patent Information
- Application Number
- CN202611149894.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
AI Technical Summary
克服了有冷缩终端附件在超高比例扩张下易应力松弛、回缩永久变形大、内部易存气孔导致绝缘击穿及轴向滑移的问题
1、通过在注塑模具型腔内壁预制对数螺旋线形微导流槽,并在充填阶段引入高压、高流速的三段速注射控制,克服了常规成型中的均质层流状态,在胶料充填变径截面时,于部件表层高效构筑了高剪切梯度的三维非均匀流场,诱导具备核壳结构的复合粒子与基胶长链沿特定流场方向定向排列。与传统无序各向同性或常规平滑模具充填相比,通过流场定向使冷缩附件在薄壁变径等应力集中区域形成各向异性的表层硬壳补强层,阻断了受外力扩张或轴向撕裂时的裂纹尖端扩展,改善了材料的抗撕裂宏观强度与拉伸形变能力。
Smart Images

Figure CN122978720A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cold shrink cable accessory manufacturing technology, specifically to a special silicone rubber for cold shrink cable terminal accessories and its preparation method. Background Technology
[0002] Cold-shrink cable termination accessories, as key components responsible for connection and insulation in power cable lines, serve for extended periods in harsh environments characterized by strong electric fields, complex outdoor climates, and overlapping mechanical tensile stresses. Polymethylvinylsiloxane silicone rubber, due to its excellent elasticity, arc resistance, and insulation properties, has become the core matrix material for manufacturing cold-shrink terminals. In practical applications, cold-shrink accessories require high-ratio radial expansion and long-term locking onto support strips, which places extremely stringent requirements on the silicone rubber's radial energy storage, tear stress resistance, resistance to permanent deformation, and microstructural uniformity.
[0003] Polymethylvinylsiloxane silicone rubber (PMSil) is a core matrix material for manufacturing cold-shrink cable termination accessories due to its excellent elasticity, arc resistance, and insulation properties. However, cold-shrink accessories require high-ratio radial expansion and long-term locking during actual service. Under long-term ultra-high strain tensile conditions, the molecular chains inside the silicone rubber are prone to stress relaxation, leading to a rapid decay of radial energy storage clamping force and inducing leakage at the cable interface. Existing technologies often use the addition of low molecular weight silicone oil to adjust rheological flowability or to coat inorganic dielectric fillers such as titanium dioxide with conventional small molecule silane coupling agents for synergistic reinforcement. However, simple physical dilution of external components or weak surface chemical bonding modification is prone to peeling failure of the modified layer during the high shear processes of mixing and injection molding. This leads to significant inorganic particle agglomeration and microphase separation within the matrix. Under long-term high strain tensile conditions, the rheological deformation becomes disordered, leaving interfacial microcracks, failing to simultaneously achieve long-term high radial energy storage, high resilience, and high tear and breakdown resistance. Therefore, how to significantly improve the long-term stress relaxation resistance, long-term radial energy storage, and tear and breakdown resistance of cold-shrinkable accessories while ensuring high-ratio radial expansion processing is a pressing technical bottleneck in this field. Therefore, a special silicone rubber for cold-shrinkable cable termination accessories and its preparation method are proposed. Summary of the Invention
[0004] The purpose of this invention is to provide a special silicone rubber for cold-shrink cable termination accessories and its preparation method. This overcomes the problems of existing cold-shrink termination accessories, such as stress relaxation under ultra-high expansion ratios, large permanent deformation due to shrinkage, and internal porosity leading to insulation breakdown and axial slippage.
[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a silicone rubber cold-shrink cable termination accessory material. The method involves the following steps: S1. Mixing process and base rubber refining Initial mixing, preheating, and seed intermediate synthesis were performed in a reactor equipped with a paddle stirrer, a high-precision temperature-controlled heating mantle, and a high-efficiency reflux condenser. First, 800 g of octamethylcyclotetrasiloxane and 200 g of tetramethyltetravinylcyclotetrasiloxane were added. Stirring was started and the speed was controlled at 200 r / min. The system was protected with high-purity nitrogen, and 0.5 g of tetramethylammonium silanolate catalyst was added. The system was heated to 110 °C to carry out a full ring-opening copolymerization reaction. During this stage, due to the difference in monomer reactivity and the equilibrium polymerization characteristics within the reactor, an active seed intermediate with a viscosity of 10000 mPa·s was obtained after 4 hours of reaction.
[0006] A continuous dropwise addition and multi-peak chain extension reaction were employed. Starting at an initial temperature of 110℃, the temperature was increased to 130℃ at a rate of 5℃ / min. Simultaneously, 500g of octamethylcyclotetrasiloxane was added dropwise at a constant rate of 10g / min using a high-precision micro-metering pump; 0.2g of tetramethylammonium silanolate catalyst was also added. The reaction was continuously stirred at 130℃ for 6 hours. After the polymerization reached equilibrium, 5g of divinyltetramethyldisiloxane was added as a capping agent, and the reaction continued for 2 hours to regulate the end groups. Through chain extension and chain transfer reactions during the dropwise addition process, mixed segments with molecular weight distributions of 25,000-30,000, 220,000-280,000, and 550,000-650,000 were induced, with corresponding number-average molecular weights of 26,000, 250,000, and 600,000, respectively, and polydispersity index (PDI) of 4.5-5.2.
[0007] After high-temperature pyrolysis and vacuum devolatilization, the system is heated to 170°C at a rate of 3°C / min. At this point, the catalyst, sodium tetramethylammonium silanolate, decomposes into volatile trimethylamine and low-molecular-weight silanolates. An axial vacuum pump with a vacuum level of -0.098 MPa is activated to forcibly remove residual unreacted trace amounts of cyclic monomers for 2 hours. The material is then cooled and discharged to obtain a special polymethylvinylsiloxane alkyl resin.
[0008] High-temperature mixing and surface passivation: 1000g of the synthesized special polymethyl vinyl siloxane rubber is added to a mixer, and the fluid heating jacket is turned on to preheat it to 58℃-62℃, preferably 60℃. Then, 240-260g of fumed silica (preferably 250g), 420-480g of the following special core-shell composite particles (preferably 450g), and 50g of hydroxyl silicone oil structure control agent are added sequentially. The mixing system is started, and the mixing speed is set to 60 r / min. Simultaneously, the rotor and cavity are rapidly heated through heat transfer oil, so that the overall temperature of the material reaches 158℃-162℃, preferably 160℃. Under this high-temperature condition, the vacuum pump is turned on, and the axial vacuum degree is adjusted to maintain an ultra-high negative pressure of -0.094MPa to -0.096MPa, preferably -0.095MPa, for 180min. During this stage, hydroxyl silicone oil undergoes a condensation reaction with free silanol groups on the surface of fumed silica, completing in-situ passivation of the surface, i.e., structural control. At the same time, the vacuum environment completely removes trace amounts of moisture, low-molecular-weight alcohols, and residual rings generated during the mixing process.
[0009] Low-temperature open milling and catalytic homogenization are performed. After the mixed materials have fully reacted, the heating system is turned off, and cooling circulating water is introduced. After the material cools to below 40°C, 45-55g of polydimethylsiloxane, preferably 50g, is added as a dilution processing aid; and 0.25-0.35g of vulcanization inhibitor 1-ethynyl-1-cyclohexanol, preferably 0.3g, is added. The material is then transferred to a stainless steel two-roll open mill. The roll gap is adjusted to 0.5mm-1.0mm, and five consecutive thin-pass operations are performed to ensure that the inhibitor is absolutely uniformly wrapped around the macromolecular chains of the base rubber under high shear force. Finally, 18-22g of highly active low-molecular-weight hydrogen-containing silicone oil, preferably 20g, is added to the open mill, wherein the active hydrogen mass fraction is strictly controlled at 1.0%; and 0.1g of platinum complex catalyst is added. The material is then repeatedly tumbled left and right on the two-roll open mill 10 times to ensure that the crosslinking agent and platinum catalyst reach a micro-molecular level homogenization. After uniform mixing, the mixture is directly sheeted, with the sheet thickness controlled at 6mm-8mm. The rubber compound is then placed in a clean room at 25℃ and relative humidity less than 40% to age in the dark for 24 hours before use.
[0010] S2, Multi-stage speed and pressure controlled injection molding The rubber compound is prepared and the equipment is prefabricated. The aged rubber compound is cut into strips and fed into the feeding and vacuum cylinder of a vertical precision silicone rubber injection molding machine. This process uses a special injection molding machine with a mold cavity. Its core feature is that the inner wall of the mold is pre-engraved with logarithmic spiral micro-guide grooves with a depth of 0.18-0.22mm, preferably 0.20mm, and a pitch of 4.5-5.5mm, preferably 5.0mm, through high-precision five-axis laser engraving.
[0011] In the high-speed filling section, the injection unit is activated, and the rubber compound is rapidly injected into the mold through the nozzle at an initial flow rate of 42-48 cm³ / s, preferably 45 cm³ / s. 3 The entire injection stroke is strictly controlled by a microcomputer, with three-stage discrete switching of speed and pressure. The screw propels the injection compound forward at a high speed of 38-42 mm / s, preferably 40 mm / s, and the injection pressure is set at 155-165 bar, preferably 160 bar. During this stage, the high shear rate and the logarithmic spiral micro-channels on the mold cavity and inner wall generate strong flow boundary layer shear forces and tensile flow fields, forcing the unsaturated silane-modified core-shell composite particles and the long molecular chains of the base rubber to align in a highly parallel orientation along the main axis of the flow field.
[0012] In the deceleration and compaction section, when the volume of the rubber compound reaches 90%-92% of the total mold cavity volume, the process immediately switches to the compaction section. The screw feed speed drops sharply to 8-12 mm / s, preferably 10 mm / s, while maintaining a medium-high pressure injection pressure of 135-145 bar, preferably 140 bar, to ensure that the rubber compound completely fills the thin-walled areas and fine parts.
[0013] In the micro-motion venting and pressure holding section, after the mold cavity is completely filled, the pressure holding stage begins. The screw maintains a micro-motion speed of 8-12 mm / s for compensation, preferably 10 mm / s, and the pressure holding pressure is set to 75-85 bar, preferably 80 bar. During the first 15 seconds of pressure holding, the injection molding machine's moving mold and stationary mold perform 2-4 micron-level rapid mold opening and closing micro-motion venting actions, preferably 3 times. Specifically, the mold is slightly opened by 0.5 mm and then quickly locked, completely expelling the trace amounts of gas generated and trapped due to high-pressure friction from the mold cavity.
[0014] The injection molding machine selected is the Ergotech 250 / 630-1200 vertical high-precision hydraulic servo injection molding machine for liquid silicone rubber manufactured by Demag. This equipment is equipped with a self-developed cold runner mold assembly, a 45mm diameter screw, and a maximum injection pressure of 220 bar. The core hydraulic control valve group has been upgraded to a German Bosch Rexroth high-frequency proportional servo valve, capable of multi-stage high-precision step switching of injection speed within 0.01 seconds. This fully meets the speed and pressure control requirements of the filling, compaction, and holding stages in the process plan, with a speed variation accuracy of ±0.1 mm / s and a pressure accuracy of ±0.5 bar. It also enables multi-point mold opening and closing precision micro-motion venting.
[0015] S3, Load-bearing secondary vulcanization and radial stress locking After isothermal in-mold co-curing and pressure holding, the mold clamping mechanism applies ultra-high clamping force. A fluid heating channel rapidly heats the mold and stabilizes it at a platform temperature of 168℃-172℃, preferably 170℃. Isothermal in-mold curing is then performed at this temperature, with the curing time controlled between 7.5-8.5 min, preferably 8.0 min. During this stage, the platinum complex catalyst is fully activated, and the silane-hydrogen bonds of the low-molecular-weight hydrogen-containing silicone oil undergo efficient hydrosilylation co-curing reactions with the vinyl groups on the main chain of the special base adhesive and the unsaturated double bonds grafted onto the surface of the core-shell composite particles, constructing a tight three-dimensional network of filler, chemical bonds, and matrix.
[0016] After a linear heating secondary vulcanization under load and in-film curing, the mold is automatically opened, and the insulating component is completely demolded by a robotic arm. Within 5 minutes of demolding, the component is fitted onto a special stainless steel long mandrel with an outer diameter matching the target cable's outer diameter, placing it in an initial pre-strained tensile state. The component with the mandrel is then moved as a whole into a high-precision hot air circulating oven with multi-directional air ducts. The hot air circulation rate is set to a constant 1.8 m / s. The oven is heated linearly at a controlled rate of 1.8℃-2.2℃ / min, preferably 2.0℃ / min, steadily increasing the temperature from room temperature to 195℃-205℃, preferably 200℃. Under this high-temperature environment, a loaded secondary vulcanization is performed for 3.5-4.5 hours, preferably 4.0 hours. This process completely drives out residual trace amounts of low-molecular-weight volatiles in the system and promotes stress relief and network reconstruction of unreacted polar groups and active bonds under tensile conditions.
[0017] After secondary vulcanization, the component is removed along with the mandrel and allowed to cool naturally for 4 hours in a standard cable manufacturing environment at 25°C, with the relative humidity controlled below 50%. Subsequently, the cured silicone rubber tubing is transferred to the expansion fixture of a high-tonnage hydraulic radial expansion device. At 25°C, it is radially stretched uniformly and smoothly to 4.5 times the actual outer diameter of the cable. While maintaining this ultra-high strain stretching state, a pre-braided, well-interlocked polypropylene spiral support strip with high axial rigidity is quickly inserted into the internal cavity of the silicone rubber tube using a pneumatic pusher. The specifications of this support strip are strictly matched to the inner diameter of the cold-shrink tube. Finally, the external expansion hydraulic pressure is slowly removed, allowing the silicone rubber component to tightly interlock and lock onto the outer wall of the polypropylene spiral support strip under its own high elastic recovery force. This produces a special silicone rubber product for cold-shrink cable terminal accessories with excellent radial energy storage and no microscopic surface defects.
[0018] Preferably, the core-shell composite particles are based on inorganic nano-vaporized silica as the core, coated with a dopamine-modified transition layer, and grown in situ on the outer layer as a dense high-dielectric titanium dioxide shell by hydrothermal growth. Finally, the surface is modified by chemical bonding through refluxing with a reactive unsaturated silane coupling agent.
[0019] Preferably, 500 mL of deionized water is added to a glass reactor equipped with a stainless steel reflux condenser. The pH of the system is fine-tuned using a 5% sodium hydroxide aqueous solution to stabilize it in a weakly alkaline environment of 8.5. 100 g of flammable silica with a native particle size of 30 nm is weighed and added to the reactor. A high-shear emulsifying disperser is turned on, and forced mechanical shear dispersion is performed at an ultra-high speed of 3000 r / min for 40 min to fully deagglomerate the silica nanoparticles in the aqueous phase, forming a uniform nano-suspension.
[0020] Subsequently, 1.7-2.5g of dopamine hydrochloride, abbreviated as PDA, was added; the mixture was stirred at a frequency of 50Hz at room temperature (25℃-35℃) for 12 hours. During this process, dopamine undergoes auto-oxidative polymerization in a weakly alkaline aqueous solution, forming a dense polydopamine transition layer rich in hydroxyl and amino groups on the surface of fumed silica, abbreviated as PDAM transition layer.
[0021] The reacted particles were centrifuged at 8000 rpm to remove excess supernatant and washed three times with deionized water. The particles with the polydopamine transition layer were then redispersed in a blend of 800 mL anhydrous ethanol and 200 mL deionized water. 20 g of tetrabutyl titanate was weighed as a titanium dioxide precursor and slowly added dropwise to the reaction vessel at a controlled rate of 1.5-2.5 mL / min using a micro-metering pump, preferably 2.0 mL / min. After the addition was complete, the system was slowly heated to 75℃-78℃, and a hydrothermal hydrolytic condensation reaction was carried out in an alcohol-water medium for 10-12 h, preferably 10 h. Tetrabutyl titanate underwent directional nucleation and hydrolytic condensation at the active sites on the polydopamine surface, resulting in the in-situ growth of a continuous and complete amorphous or microcrystalline titanium dioxide shell.
[0022] Finally, 2.44 g of the unsaturated silane coupling agent γ-methacryloxypropyltrimethoxysilane was directly added to the system, corresponding to 2% of the total monomer mass. The system was controlled at 60 °C for reflux surface modification reaction for 2.5-3.5 h, preferably 3 h. The alkoxy end of the silane coupling agent underwent de-alcoholization condensation with the hydroxyl groups on the titanium dioxide surface, while the methacryloxy end with the unsaturated double bond was exposed. After the reaction, the mixture was filtered through a graded plate and frame filter, vacuum dried in a vacuum oven at 105 °C and a vacuum degree of -0.095 MPa for 24 h, and then deeply ground by a stainless steel air jet mill and passed through a 500-mesh microporous sieve to obtain core-shell composite particles.
[0023] The raw materials used in this invention are as follows: Fumed silica: commonly known as white carbon black, purchased from Wacker Chemie, commercial model HDK® N20. Native particle size 7-15 nm, specific surface area determined by BET method 200±25 m² / g, pH value 3.8-4.3, total silica content greater than or equal to 99.8%, and loss on heating at 105℃ for 2 hours less than or equal to 1.5%.
[0024] Dopamine hydrochloride, abbreviated as PDA, was purchased from Aladdin Reagents, commercial model H104523. It was analytical grade (AR grade), with a purity greater than or equal to 98.0%, and a melting point of 247℃-249℃. Tetrabutyl titanate, abbreviated as TBT, was purchased from Sinopharm Chemical Reagent Co., Ltd., quality grade chemically pure, with a titanium dioxide content of 23.0%-23.5%, density of 0.996 g / cm³, and refractive index of 1.491. γ-Methacryloxypropyltrimethoxysilane, as an unsaturated silane coupling agent, was purchased from Momentive Advanced Materials, commercial model A-174, with a purity ≥98.5%, molecular weight of 248.3, boiling point of 255℃, and flash point of 108℃. Hydroxyl silicone oil, used as a structure control agent, was purchased from Bluestar Organosilicon, model SD-207. Its viscosity at 25℃ was 25-35 mPa·s, with a hydroxyl content of 8.5%-9.2% by mass, and a volatile content of less than or equal to 1.0% after 3 hours at 150℃. Polydimethylsiloxane, used as a processing oil additive, was purchased from Shin-Etsu Chemical, commercial model KF-96-100cs. Its kinematic viscosity was 100±5 mm² / s, flash point was greater than 300℃, and specific gravity was 0.965. The vulcanization inhibitor was specifically 1-ethynyl-1-cyclohexanol, CAS number 78-27-3, purity ≥99.0%, melting point 30℃-33℃, and boiling point 180℃. Low-molecular-weight hydrogen-containing silicone oil, purchased from Shin-Etsu Chemical (commercial model KF-99), was used as a crosslinking agent. It had an active hydrogen content of 1.02%, a viscosity of 20-30 mPa·s at 25°C, and a volatile content ≤0.5% after 2 hours at 150°C. It was a clear, colorless, and transparent liquid. The platinum complex catalyst, namely the Karstedt catalyst, was purchased from Momentive Advanced Materials (commercial model SilForce™ UV9390C). It had an active platinum metal content of 3000 ppm, an acid value ≤0.005 mg KOH / g, and exhibited excellent solubility in silicone rubber-based adhesives.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. By prefabricating logarithmic spiral micro-guide channels on the inner wall of the injection mold cavity and introducing high-pressure, high-flow-rate three-stage injection control during the filling stage, the homogeneous laminar flow state in conventional molding is overcome. When the rubber fills the variable-diameter section, a three-dimensional non-uniform flow field with a high shear gradient is efficiently constructed on the surface of the part, inducing composite particles with core-shell structures and long chains of base rubber to oriented along a specific flow field direction. Compared with traditional disordered isotropic or conventional smooth mold filling, the flow field orientation enables the cold shrinkage attachment to form an anisotropic surface hard shell reinforcement layer in stress concentration areas such as thin-walled variable-diameter areas, blocking the crack tip propagation when subjected to external force expansion or axial tearing, and improving the material's macroscopic tear resistance and tensile deformation capacity.
[0026] 2. The formulation incorporates a special polymethylvinylsiloxane rubber with multiple molecular weights, and introduces core-shell composite particles modified by dopamine interlayer co-vulcanization during mixing. After molding, it undergoes a specific multi-stage high-temperature circulating hot air secondary vulcanization. This achieves strong interfacial anchoring between the filler surface and the silicone rubber matrix, and deeply eliminates macromolecular residual stress and microstructural defects within the cross-linked network. Under long-term strain conditions with high-ratio radial expansion, it can effectively constrain the conformational relaxation and microscopic viscous deformation slip of macromolecular segments, overcoming the network deentanglement behavior caused by interfacial debonding or insufficient vulcanization in existing technologies, and significantly reducing the shrinkage permanent deformation rate under room temperature and thermal aging environments.
[0027] 3. By introducing a modified and complete titanium dioxide / silica core-shell structure, and performing multiple rapid mold opening and closing micro-movement venting during the injection molding and holding pressure stage, combined with subsequent high-temperature hot air circulation secondary vulcanization, the high-dielectric shell layer uniformly disperses the terminal electric field stress while completely eliminating micropore defects caused by gas retention inside the rubber material, and forcibly removing residual free polar small molecules in the system. Compared with conventional molding processes, this eliminates discontinuities inside the dielectric under high-voltage alternating electric fields, effectively suppresses partial discharge and electron avalanche channels caused by abrupt changes in the porous dielectric, and blocks the migration and polarization losses of free ions under strong electric fields, enabling the material to maintain high power frequency breakdown strength while exhibiting low dielectric loss response.
[0028] 4. By optimizing the total content of fumed silica and core-shell composite particles, and utilizing the spatial superposition of a high-rigidity inorganic framework and high-density co-sulfurized chemical crosslinking points, a composite network with synergistic high hardness and high elastic deformation recovery force is constructed. When the cold-shrink accessories are fitted onto the outer wall of the cable's main insulation, this network transforms large expansion deformation into long-lasting normal elastic contraction stress, delaying the physical stress relaxation behavior of the polymer chain segments. Furthermore, the dense chemical network and defect-free surface structure increase the microscopic frictional resistance at the interface with crosslinked polyethylene, preventing reverse lubrication slippage caused by the release of low-molecular-weight substances. This ensures a simultaneous increase in macroscopic sealing pressure and axial mechanical engagement resistance, preventing moisture intrusion and accessory displacement during operation. Attached Figure Description
[0029] Figure 1 The Fourier Transform Infrared (FTIR) characterization spectrum of the special polymethylvinylsiloxane adhesive prepared for the embodiments of the present invention; Figure 2 A schematic diagram of the macroscopic structure and partial cross-sectional view of the special silicone rubber product for cold-shrink cable terminal accessories prepared according to an embodiment of the present invention in its expanded state; Figure 3 This is a comparison chart of the mechanical strength test results of various embodiments and comparative examples of the present invention in Test Example 1, including the dual Y-axis distribution and error distribution of elongation at break and tear strength. Detailed Implementation
[0030] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims. Please refer to... Figures 1 to 3 This invention provides a special silicone rubber for cold-shrink cable termination accessories and its preparation method. The technical solution is as follows: 800g of octamethylcyclotetrasiloxane and 200g of tetramethyltetravinylcyclotetrasiloxane were added to a reactor, along with 0.5g of tetramethylammonium silanolate catalyst. The reaction was carried out at 110℃ with stirring at 200r / min and reflux for 4 hours to obtain an active seed with a viscosity of 10000mPa·s. The initial temperature of 110℃ was increased to 130℃ at a rate of 5℃ / min, while 500g of octamethylcyclotetrasiloxane was added dropwise at a constant rate of 10g / min. 0.2g of tetramethylammonium silanolate was also added, and the reaction was stirred continuously for 6 hours. After the polymerization reaction reached equilibrium, 5g of divinyltetramethyldisiloxane was added as a capping agent, and the reaction was continued for 2 hours to regulate the end groups. The system was then heated to 170℃ at a rate of 3℃ / min, and a vacuum device with a vacuum degree of -0.098MPa was activated to forcibly remove residual monomers for 2 hours to obtain a special polymethylvinylsiloxane adhesive.
[0031] The special polymethylvinylsiloxane adhesive prepared in Example 1 was characterized by Fourier transform infrared spectroscopy (FTIR) using a total reflectance ATR Fourier transform infrared spectrometer with a scanning range of 4000-400 cm⁻¹ and a resolution of 4 cm⁻¹. -1 The signal accumulation scan was performed 32 times, the ambient temperature was 25℃, and the relative humidity was 48%. The test results are as follows: Figure 1 As shown.
[0032] See Figure 1 At wavenumbers of 1000-1100 cm⁻¹ -1 A very deep and broad double peak with strong splitting appeared at 1260 cm⁻¹, corresponding to the asymmetric stretching vibration peak of the Si-O-Si backbone in the matrix adhesive; at 1260 cm⁻¹... -1 A sharp and strong absorption peak is observed at 1600 cm⁻¹, corresponding to the symmetric deformation vibration of Si-CH₃; particularly, at 1600 cm⁻¹... -1 and 1410cm -1 Weak but microscopically sharp characteristic absorption peaks can be clearly observed at all locations, confirming the successful introduction of the C=C stretching vibration of the -CH=CH2 vinyl group in tetramethyltetravinylcyclotetrasiloxane into the main chain. Furthermore, at a high wavenumber of 2960 cm⁻¹... -1 A stretching vibration peak of saturated CH was observed at [location]. Figure 1 The waveform and characteristic peak distribution confirm that the present invention successfully constructed a base glue system with a pre-defined functional group structure through a seed chain extension process.
[0033] Example 1 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated at 3000 r / min for 40 min. 2 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 25 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 20 g of tetrabutyl titanate was weighed and added dropwise at a rate of 2 mL / min. The mixture was heated to 75 °C for hydrothermal reaction for 10 h. Finally, 2.44 g (corresponding to 2% of the total monomer mass) of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 3 h for modification. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0034] 1000g of the above-mentioned polymethylvinylsiloxane rubber was put into a mixer and preheated to 60°C. Then, 250g of fumed silica, 450g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added in sequence. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 160°C. The mixture was kept under a vacuum of -0.095MPa for 180min. After the material cooled to 40°C, 50g of polydimethylsiloxane and 0.3g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill 5 times. Finally, 20g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen mass fraction of 1.0% and 0.1g of platinum complex catalyst were added. After repeated mixing and homogenization, the mixture was sheeted out.
[0035] A special injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide grooves with a depth of 0.2mm and a pitch of 5mm. The injection unit is started, and the rubber material is injected at a speed of 45cm. 3 The initial flow rate is injected into the mold at 40 mm / s. The injection process is divided into three speed control stages: filling stage - injecting the material at a speed of 40 mm / s and setting the injection pressure to 160 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - reducing the speed to 10 mm / s and maintaining an injection pressure of 140 bar; holding stage - injecting at 10 mm / s and setting the pressure to 80 bar, performing three rapid mold opening and closing cycles to release air.
[0036] The mold is heated to 170℃ and vulcanized at a constant temperature for 8 minutes for in-mold molding. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is then raised to 200℃ at a rate of 2℃ / min for a second vulcanization for 4 hours. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable using a radial expansion device at 25℃. A matching polypropylene spiral support strip is then quickly inserted to obtain the special silicone rubber for cold-shrink cable terminal accessories. See also: Figure 2 The accessory presents itself as a multi-layered, variable-diameter silicone rubber tubular insulating sleeve. Due to the aforementioned mold cavity and three-stage rapid injection molding process, the rubber matrix exhibits a high degree of orientation of the molecular chains and core-shell filler along the flow field direction, macroscopically displaying a matte yet tough high-strain elastic deformation state. Inside the sleeve, a continuously spirally wound polypropylene plastic spiral support strip is tightly inserted, through... Figure 2 As can be seen from the partial cut-angle section, the PP support strips form a highly rigid interlocking structure, which can stably support and lock the silicone rubber tube after undergoing a 4.5 times radial ultra-high ratio expansion, so that there are no microscopic pore defects on its surface, and the component has excellent radial energy storage and clamping force under long-term expansion.
[0037] Example 2 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated with a high-shear disperser at 3000 r / min for 40 min. 1.8 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 28 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 18 g of tetrabutyl titanate was weighed and added dropwise at a rate of 1.5 mL / min. The mixture was heated to 75 °C for hydrothermal reaction for 11 h. Finally, 2.2 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 2.5 h for modification. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0038] 1000g of the above-mentioned polymethylvinylsiloxane rubber was put into a mixer and preheated to 58°C. Then, 240g of fumed silica, 420g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added in sequence. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 158°C. The mixture was kept under a vacuum of -0.094MPa for 180min. After the material cooled to 40°C, 45g of polydimethylsiloxane and 0.25g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill 5 times. Finally, 18g of low molecular weight hydrogen-containing silicone oil with an active hydrogen mass fraction of 1.0% and 0.1g of platinum complex catalyst were added. After repeated mixing and homogenization, the mixture was sheeted out.
[0039] A special injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide grooves with a depth of 0.18mm and a pitch of 5.5mm. The injection unit is started, and the rubber material is injected at a speed of 42cm. 3 The initial flow rate is 38 mm / s when injected into the mold. The injection process is divided into three speed control stages: filling stage - the material is injected at a speed of 38 mm / s and the injection pressure is set to 155 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - the speed is reduced to 8 mm / s while maintaining an injection pressure of 135 bar; holding stage - the injection speed is 8 mm / s while the pressure is set to 75 bar, and two rapid mold opening and closing operations are performed to release air.
[0040] The mold is heated to 168℃ and vulcanized at a constant temperature for 7.5 minutes for in-mold molding. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is raised to 195℃ at a rate of 1.8℃ / min for a second vulcanization for 3.5 hours. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable at 25℃ using a radial expansion device. A polypropylene spiral support strip matching the model is quickly inserted to obtain special silicone rubber for cold shrink cable terminal accessories.
[0041] Example 3 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated with a high-shear disperser at 3000 r / min for 40 min. 2.2 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 32 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 22 g of tetrabutyl titanate was weighed and added dropwise at a rate of 2.5 mL / min. The mixture was heated to 78 °C for hydrothermal reaction for 12 h. Finally, 2.6 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 3.5 h for modification. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0042] 1000g of the above-mentioned polymethylvinylsiloxane rubber was put into a mixer and preheated to 62°C. Then, 260g of fumed silica, 480g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added in sequence. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 162°C. The mixture was kept under a vacuum of -0.096MPa for 180min. After the material cooled to 40°C, 55g of polydimethylsiloxane and 0.35g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill 5 times. Finally, 22g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen mass fraction of 1.0% and 0.1g of platinum complex catalyst were added. After repeated mixing and homogenization, the mixture was sheeted out.
[0043] A specialized injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-channels with a depth of 0.22mm and a pitch of 4.5mm. The injection unit is started, and the plastic material is injected at a rate of 48cm... 3 The initial flow rate is injected into the mold at 42 mm / s. The injection process is divided into three speed control stages: filling stage - the material is injected at a speed of 42 mm / s and the injection pressure is set to 165 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - the speed is reduced to 12 mm / s while maintaining an injection pressure of 145 bar; holding stage - the injection is performed at 12 mm / s while the pressure is set to 85 bar, and four rapid mold opening and closing cycles are executed to release air.
[0044] The mold is heated to 172℃ and vulcanized at a constant temperature for 8.5 minutes for in-mold molding. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is raised to 205℃ at a rate of 2.2℃ / min for a second vulcanization of 4.5 hours. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable at 25℃ using a radial expansion device. A polypropylene spiral support strip matching the model is quickly inserted to obtain special silicone rubber for cold shrink cable terminal accessories.
[0045] Example 4 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated with a high-shear disperser at 3000 r / min for 40 min. 1.9 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 26 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 19 g of tetrabutyl titanate was weighed and added dropwise at a rate of 1.8 mL / min. The mixture was heated to 78 °C for hydrothermal reaction for 9 h. Finally, 2.3 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 2.8 h for modification. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0046] 1000g of the above-mentioned polymethylvinylsiloxane rubber was put into a mixer and preheated to 56°C. Then, 230g of fumed silica, 435g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added in sequence. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 155°C. The mixture was kept under a vacuum of -0.093MPa for 180min. After the material cooled to 40°C, 40g of polydimethylsiloxane and 0.28g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill 5 times. Finally, 19g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen mass fraction of 1.0% and 0.1g of platinum complex catalyst were added. After repeated mixing and homogenization, the mixture was sheeted out.
[0047] A special injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide grooves with a depth of 0.15mm and a pitch of 6.0mm. The injection unit is started, and the rubber material is injected at a rate of 41cm. 3 The initial flow rate is injected into the mold at 35 mm / s. The injection process is divided into three speed control stages: filling stage - injecting the material at a speed of 35 mm / s and setting the injection pressure to 150 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - reducing the speed to 9 mm / s and maintaining an injection pressure of 130 bar; holding stage - injecting at 9 mm / s and setting the pressure to 70 bar, performing two rapid mold opening and closing venting operations.
[0048] The mold is heated to 165℃ and vulcanized at a constant temperature for 7.0 min for in-mold molding. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is raised to 190℃ at a rate of 1.5℃ / min for a second vulcanization for 3.0 h. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable at 25℃ using a radial expansion device. A polypropylene spiral support strip matching the model is quickly inserted to obtain special silicone rubber for cold shrink cable terminal accessories.
[0049] Example 5 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated with a high-shear disperser at 3000 r / min for 40 min. 2.1 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 30 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 21 g of tetrabutyl titanate was weighed and added dropwise at a rate of 2.2 mL / min. The mixture was heated to 76 °C for hydrothermal reaction for 13 h. Finally, 2.5 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 3.2 h for modification. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0050] 1000g of the above-mentioned polymethylvinylsiloxane rubber was put into a mixer and preheated to 64°C. Then, 270g of fumed silica, 465g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added in sequence. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 165°C. The mixture was kept under a vacuum of -0.097MPa for 180min. After the material cooled to 40°C, 60g of polydimethylsiloxane and 0.32g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill 5 times. Finally, 21g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen mass fraction of 1.0% and 0.1g of platinum complex catalyst were added. After repeated mixing and homogenization, the mixture was sheeted out.
[0051] A special injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide channels with a depth of 0.25mm and a pitch of 4.0mm. The injection unit is started, and the plastic material is injected at a rate of 49cm... 3The initial flow rate is injected into the mold at 45 mm / s. The injection process is divided into three speed control stages: filling stage - injecting the material at a speed of 45 mm / s and setting the injection pressure to 170 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - reducing the speed to 11 mm / s and maintaining an injection pressure of 150 bar; holding stage - injecting at 11 mm / s while setting the pressure to 90 bar and performing 5 rapid mold opening and closing cycles for venting.
[0052] The mold is heated to 175℃ and vulcanized at a constant temperature for 9.0 min for in-mold molding. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is raised to 210℃ at a rate of 2.5℃ / min for 5.0 h of secondary vulcanization. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable at 25℃ using a radial expansion device. A polypropylene spiral support strip matching the model is quickly inserted to obtain special silicone rubber for cold shrink cable terminal accessories.
[0053] Example 6 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated with a high-shear disperser at 3000 r / min for 40 min. 1.7 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 24 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 17 g of tetrabutyl titanate was weighed and added dropwise at a rate of 1.2 mL / min. The mixture was heated to 78 °C for hydrothermal reaction for 8 h. Finally, 2.1 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 2.2 h for modification. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0054] 1000g of the above-mentioned polymethylvinylsiloxane rubber was put into a mixer and preheated to 55°C. Then, 220g of fumed silica, 410g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added in sequence. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 152°C. The mixture was kept under a vacuum of -0.092MPa for 180min. After the material cooled to 40°C, 35g of polydimethylsiloxane and 0.22g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill 5 times. Finally, 17g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen mass fraction of 1.0% and 0.1g of platinum complex catalyst were added. After repeated mixing and homogenization, the mixture was sheeted out.
[0055] A special injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide channels with a depth of 0.12mm and a pitch of 6.5mm. The injection unit is started, and the plastic material is injected at a rate of 40cm... 3 The initial flow rate is 32 mm / s when injected into the mold. The injection process is divided into three speed control stages: filling stage - the material is injected at a speed of 32 mm / s and the injection pressure is set to 145 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - the speed is reduced to 7 mm / s while maintaining an injection pressure of 125 bar; holding stage - the injection is performed at 7 mm / s while the pressure is set to 65 bar, and one rapid mold opening and closing is performed to vent the air.
[0056] The mold is heated to 162℃ and vulcanized at a constant temperature for 6.5 minutes for in-mold molding. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is raised to 185℃ at a rate of 1.2℃ / min for 2.5 hours of secondary vulcanization. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable at 25℃ using a radial expansion device. A polypropylene spiral support strip matching the model is quickly inserted to obtain special silicone rubber for cold shrink cable terminal accessories.
[0057] Example 7 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated with a high-shear disperser at 3000 r / min for 40 min. 2.3 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 34 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 23 g of tetrabutyl titanate was weighed and added dropwise at a rate of 2.8 mL / min. The mixture was heated to 78 °C for hydrothermal reaction for 14 h. Finally, 2.7 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 3.8 h. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0058] 1000g of the above-mentioned polymethylvinylsiloxane rubber was added to a mixer and preheated to 66°C. Then, 255g of fumed silica, 440g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added sequentially. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 168°C. The mixture was then held under a vacuum of -0.098MPa for 180min. After the material cooled to 40°C, 65g of polydimethylsiloxane and 0.38g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill five times. Finally, 23g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen content of 1.0% and 0.1g of platinum complex catalyst were added. The mixture was repeatedly kneaded until homogeneous before sheeting.
[0059] A special injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide grooves with a depth of 0.28 mm and a pitch of 3.5 mm. The injection unit is started, and the plastic material is injected at a rate of 50 cm... 3 The initial flow rate is 48 mm / s when injected into the mold. The injection process is divided into three speed control stages: filling stage - the material is injected at a speed of 48 mm / s and the injection pressure is set to 175 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - the speed is reduced to 13 mm / s while maintaining an injection pressure of 155 bar; holding stage - the injection is performed at 13 mm / s while the pressure is set to 95 bar, and six rapid mold opening and closing cycles are executed to release air.
[0060] The mold is heated to 178℃ and vulcanized at a constant temperature for 9.5 minutes for in-mold molding. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is raised to 215℃ at a rate of 2.8℃ / min for a second vulcanization of 5.5 hours. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable at 25℃ using a radial expansion device. A polypropylene spiral support strip matching the model is quickly inserted to obtain special silicone rubber for cold shrink cable terminal accessories.
[0061] Example 8 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated with a high-shear disperser at 3000 r / min for 40 min. 2.4 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 35 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 24 g of tetrabutyl titanate was weighed and added dropwise at a rate of 3.0 mL / min. The mixture was heated to 75 °C for hydrothermal reaction for 15 h. Finally, 2.8 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 4.0 h. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0062] 1000g of the above-mentioned polymethylvinylsiloxane rubber was added to a mixer and preheated to 68°C. Then, 280g of fumed silica, 475g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added sequentially. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 170°C. The mixture was then held under a vacuum of -0.099MPa for 180min. After the material cooled to 40°C, 70g of polydimethylsiloxane and 0.40g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill five times. Finally, 24g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen content of 1.0% and 0.1g of platinum complex catalyst were added. After repeated mixing until homogeneous, the mixture was sheeted.
[0063] A special injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide channels with a depth of 0.30 mm and a pitch of 3.0 mm. The injection unit is started, and the plastic material is injected at a rate of 52 cm. 3 The initial flow rate is injected into the mold at 50 mm / s. The injection process is divided into three speed control stages: filling stage - injecting the material at a speed of 50 mm / s and setting the injection pressure to 180 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - reducing the speed to 15 mm / s and maintaining an injection pressure of 160 bar; holding stage - injecting at 15 mm / s while setting the pressure to 100 bar and performing 7 rapid mold opening and closing venting operations.
[0064] The mold is heated to 180℃ and vulcanized at a constant temperature for 10.0 min for in-mold molding. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is raised to 220℃ at a rate of 3.0℃ / min for 6.0 h of secondary vulcanization. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable at 25℃ using a radial expansion device. A polypropylene spiral support strip matching the model is quickly inserted to obtain special silicone rubber for cold shrink cable terminal accessories.
[0065] Example 9 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated with a high-shear disperser at 3000 r / min for 40 min. 2.0 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 29 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 20.5 g of tetrabutyl titanate was weighed and added dropwise at a rate of 2.0 mL / min. The mixture was heated to 75 °C for hydrothermal reaction for 10.5 h. Finally, 2.4 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 3.0 h. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0066] 1000g of the above-mentioned polymethylvinylsiloxane rubber was added to a mixer and preheated to 61°C. Then, 245g of fumed silica, 455g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added sequentially. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 161°C. The mixture was then held under a vacuum of -0.095MPa for 180min. After the material cooled to 40°C, 48g of polydimethylsiloxane and 0.29g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill five times. Finally, 19.5g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen content of 1.0% and 0.1g of platinum complex catalyst were added. After repeated mixing until homogeneous, the mixture was sheeted.
[0067] A special injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide channels with a depth of 0.21 mm and a pitch of 5.2 mm. The injection unit is started, and the plastic material is injected at a rate of 44 cm... 3 The initial flow rate is 40 mm / s when injected into the mold. The injection process is divided into three speed control stages: filling stage - the material is injected at a speed of 40 mm / s and the injection pressure is set to 162 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - the speed is reduced to 9.5 mm / s while maintaining an injection pressure of 138 bar; holding stage - the injection is performed at 9.5 mm / s while the pressure is set to 78 bar, and three rapid mold opening and closing cycles are executed to release air.
[0068] The mold is heated to 171℃ and in-mold vulcanized for 8.2 minutes. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is raised to 198℃ at a rate of 2.0℃ / min for a second vulcanization of 4.2 hours. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable at 25℃ using a radial expansion device. A polypropylene spiral support strip matching the model is quickly inserted to obtain special silicone rubber for cold shrink cable terminal accessories.
[0069] Example 10 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of fumed silica with a particle size of 30 nm was weighed and added to a disperser, and treated with a high-shear disperser at 3000 r / min for 40 min. 2.5 g of dopamine hydrochloride was added, and the mixture was stirred at 50 Hz for 12 h at 36 °C. After centrifugation and washing, the particles were redispersed in a mixed solvent of 800 mL of anhydrous ethanol and 200 mL of deionized water. 25 g of tetrabutyl titanate was weighed and added dropwise at a rate of 3.5 mL / min. The mixture was heated to 78 °C for hydrothermal reaction for 16 h. Finally, 2.9 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 5.0 h. After filtration, vacuum drying, and grinding, core-shell composite particles were obtained.
[0070] 1000g of the above-mentioned polymethylvinylsiloxane rubber was added to a mixer and preheated to 70°C. Then, 265g of fumed silica, 490g of the prepared core-shell composite particles, and 50g of hydroxyl silicone oil were added sequentially. The mixer system was started, the speed was set to 60r / min, and the temperature was raised to 172°C. The mixture was then maintained under a vacuum of -0.100MPa for 180min. After the material cooled to 40°C, 75g of polydimethylsiloxane and 0.45g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was then passed through a two-roll mill five times. Finally, 25g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen content of 1.0% and 0.1g of platinum complex catalyst were added. The mixture was repeatedly kneaded until homogeneous before sheeting.
[0071] A special injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide channels with a depth of 0.35mm and a pitch of 2.5mm. The injection unit is started, and the plastic material is injected at a rate of 55cm... 3 The initial flow rate is injected into the mold at 55 mm / s. The injection process is divided into three speed control stages: filling stage - the material is injected at a speed of 55 mm / s and the injection pressure is set to 190 bar to induce the core-shell filler to oriented along the flow direction; compaction stage - the speed is reduced to 16 mm / s while maintaining an injection pressure of 170 bar; holding stage - the injection is performed at 16 mm / s while the pressure is set to 110 bar, and 8 rapid mold opening and closing cycles are executed to release air.
[0072] The mold is heated to 185℃ and vulcanized at a constant temperature for 12.0 min for in-mold molding. After demolding, the part is inserted into the mandrel and placed in an oven with a hot air circulation rate of 1.8 m / s. The temperature is then raised to 225℃ at a rate of 3.5℃ / min for a second vulcanization for 7.0 h. Finally, the finished product is radially stretched to 4.5 times the outer diameter of the cable using a radial expansion device at 25℃. A matching polypropylene spiral support strip is then quickly inserted to obtain the special silicone rubber for cold-shrink cable terminal accessories.
[0073] Comparative Example 1 In a reactor equipped with a reflux condenser, 500 mL of deionized water was added, and the pH of the system was adjusted to 8.5 using a 5% sodium hydroxide aqueous solution. 100 g of 30 nm fumed silica was weighed and added to a disperser, and treated using a high-shear disperser at 3000 rpm for 40 min. After centrifugation and washing, the particles were redispersed in a mixture of 800 mL of anhydrous ethanol and 200 mL of deionized water. Dopamine hydrochloride was not added during this step. 20 g of tetrabutyl titanate was weighed and added dropwise at a rate of 2 mL / min, and the mixture was heated to 75 °C for a hydrothermal reaction for 10 h. Finally, 2.44 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was refluxed at 60 °C for 3 h for modification. After filtration, vacuum drying, and grinding, composite particles were obtained.
[0074] 1000g of the above-mentioned polymethylvinylsiloxane was added to a mixer and preheated to 60°C. Then, 250g of fumed silica, 450g of the prepared composite particles, and 50g of hydroxyl silicone oil were added sequentially. The mixer was started, the speed was set to 60r / min, and the temperature was raised to 160°C. The mixture was then held under a vacuum of -0.095MPa for 180min. After the material cooled to 40°C, 50g of polydimethylsiloxane and 0.3g of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol were added. The mixture was passed through a two-roll mill five times. Finally, 20g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen content of 1.0% and 0.1g of platinum complex catalyst were added. After repeated mixing until homogeneous, the mixture was sheeted.
[0075] The subsequent injection molding, vulcanization molding, secondary vulcanization and expansion steps are exactly the same as in Example 1.
[0076] Comparative Example 2 The raw material ratio, base rubber preparation, core-shell composite particle preparation, and mixing and sheeting steps are exactly the same as those in Example 1.
[0077] A specialized injection molding machine with a mold cavity is used. The inner wall of the mold has pre-fabricated logarithmic spiral micro-guide channels with a depth of 0.2 mm and a pitch of 5 mm. The injection unit is started, injecting the plastic material into the mold at an initial flow rate of 45 cm³ / s. No three-stage speed control is used during the injection process; the plastic material is injected at a constant speed of 10 mm / s throughout, and the injection pressure is maintained at a constant 140 bar throughout the process.
[0078] The subsequent vulcanization molding, secondary vulcanization and expansion steps are exactly the same as in Example 1.
[0079] Comparative Example 3 The preparation and pre-mixing steps of the core-shell composite particles are exactly the same as those in Example 1.
[0080] In the functional additive stage, 1000g of base rubber was preheated to 60℃, and 250g of fumed silica, 450g of core-shell composite particles, and 50g of hydroxyl silicone oil were added. The mixture was then heated to 160℃ and vacuum-mixed. After cooling to 40℃, 50g of polydimethylsiloxane and 0.3g of inhibitor were added. Finally, 5g of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen content of 1.0% and 0.1g of platinum complex catalyst were added.
[0081] The subsequent injection molding and vulcanization steps are exactly the same as in Example 1.
[0082] Comparative Example 4 The raw material preparation, mixing process, and injection molding process are exactly the same as those in Example 1.
[0083] The mold is heated to 170℃ and vulcanized at a constant temperature for 8 minutes for in-mold molding. After demolding, no secondary vulcanization is performed. Instead, the finished product is directly stretched radially to 4.5 times the outer diameter of the cable using a radial expansion device at 25℃, and then quickly inserted into the support strip.
[0084] Comparative Example 5 The raw material preparation and mixing process are exactly the same as those in Example 1.
[0085] A special injection molding machine with a mold cavity is used. The inner wall of the mold is a smooth surface, and no logarithmic spiral micro-guide grooves are pre-made, i.e., the depth is 0. The injection unit is started, and the remaining injection speed control parameters, vulcanization parameters, and expansion parameters are exactly the same as in Example 1.
[0086] Test Example 1 This test aims to assess the ability of vulcanizates to resist tensile failure and crack propagation under external forces. It is a core indicator for evaluating the orientation reinforcement efficiency of core-shell fillers. Tensile specimens are made by molding or cutting 2.0 mm thick sheets from injection-molded finished parts (axial and radial). The specimens are punched using a standard punching machine and a Type I dumbbell-shaped punch conforming to GB / T 528-2009. The gauge length of the specimen is 25 mm, and the tensile speed is 500 mm / min.
[0087] Tear test specimens were prepared by punching 2.0 mm thick, uncut right-angled specimens using a right-angle punch, conforming to GB / T 529-2008. Testing was performed using an electronic universal tensile testing machine. The specimens were conditioned for at least 16 hours in a standard laboratory environment at 23℃ and 50% relative humidity. The thickness and width of the narrow parallel sections of the test specimens were measured using a thickness gauge, with at least three measurements taken per group. The median value was used to calculate the cross-sectional area A. The thickness d at the right-angle vertex of the tear specimen was measured. The specimens were symmetrically clamped in the upper and lower fixtures of the tensile testing machine. The initial fixture spacing was set to 50 mm at the tensile position, and the tensile speed was uniformly set to 500 mm / min. The tensile testing machine was started, and the extensometer tracked the gauge length change in real time. The load F when the specimen was stretched to 300% elongation was recorded. 300 The maximum load F at which the specimen breaks b and the gauge length L at the time of fracture b The tear test records the maximum tear load F during the specimen failure process. max .
[0088] , , The test results are shown in Table 1 and Figure 3 As shown.
[0089] Table 1 As can be seen from the test data in Table 1, Examples 1, 2, and 3 exhibit excellent comprehensive mechanical properties, with elongation at break all remaining above 800% and tear strength greater than 48 kN / m. The base adhesive was induced to form mixed segments through stepwise polymerization. High molecular weight segments provide an ultra-high entanglement network, giving the vulcanizate extremely high elongation at break and tear strength; low molecular weight segments improve the flowability of the compound and help the filler to align anisotropically under shear field; composite particles with fumed silica as the core, dopamine layer as the transition, and titanium dioxide as the shell, after being modified with silane coupling agent, have their methacryloyloxy groups on the particle surface participate in co-vulcanization reaction with vinyl groups in the base rubber under platinum catalysis, forming a strong interfacial bond between filler, chemical bond, and matrix, significantly improving the tensile stress and tear strength by 300%; and the use of a mold with logarithmic spiral micro-channels, and the use of a high initial flow rate in the injection filling section, along with the filling speed and high injection pressure, introduces a strong shear flow and tensile flow field in the mold cavity, forcing the core-shell filler with high aspect ratio or microstructure orientation to align oriented along the flow field direction, achieving structural reinforcement along the radial and axial directions of the cable.
[0090] Figure 3The bar chart corresponding to the left vertical axis clearly shows the fluctuation of elongation at break for each group, while the line graph on the right vertical axis shows the nonlinear change in tear strength. As can be seen from the figures, the bar height and line graph data points of Examples 1-3 are significantly better than those of the comparative examples, indicating the use of multi-point sampling tests. Specifically, Comparative Example 1, lacking a dopamine-mediated layer, suffers from interfacial debonding, resulting in extremely low bar height and line graph levels. Comparative Example 2, lacking flow field directional reinforcement, fails to achieve a step increase in strength. Comparative Example 5, with its mold lacking micro-channels, exhibits significantly lower tear resistance line graphs at thin walls compared to Example 1 due to edge laminar shear degradation. Specifically, Comparative Example 1, lacking a PDA intermediate mediator layer, suffers from uneven growth and easy peeling of the titanium dioxide shell on the fumed silica surface, leading to a low coupling agent grafting rate. During mixing, the filler undergoes nanoscale agglomeration, resulting in extremely weak interfacial bonding with the base adhesive. Under external tensile force, these agglomerates become stress concentration points and induce microcracks, leading to a comprehensive reduction in overall mechanical properties. Comparative Example 2: Low-speed injection throughout resulted in insufficient shear rate, failing to induce the core-shell filler and base rubber long chains to oriented during injection molding. Simultaneously, the lack of high-frequency venting in the holding pressure section caused trace amounts of volatiles to be trapped inside the product, forming micropore defects. During stretching and tearing, the disordered filler distribution could not effectively hinder crack propagation, and stress concentration at the micropores led to premature product fracture. Comparative Example 3: The smooth inner wall of the mold allowed for conventional laminar flow during material filling, significantly reducing the local shear gradient near the mold wall edge. This resulted in insufficient filler orientation on the surface of the component, failing to form a laminar-oriented hard-shell reinforcing layer, thus weakening the tear and expansion resistance at the thin-walled diameter change of the cold-shrink fitting.
[0091] Test Example 2 This test is used to evaluate the creep resistance and heat aging resistance of cold shrink tubing under long-term high strain expansion, and to determine the aging stability of the cable accessory's clamping force. The initial inner diameter of the tubing sample is measured at four points along the circumference at the axial middle position using a vernier caliper, and the average value is taken as D0. At 25°C, the tubing sample is forcibly expanded radially using a mechanical support frame and fitted onto a mandrel with an outer diameter of D1. The expanded state is maintained for 24 hours. After the time is reached, the mandrel is quickly removed to release the sample, allowing it to freely rebound and adjust for 5 minutes under standard room temperature conditions. The inner diameter of the sample was measured again, and the average value from multiple points was taken as the inner diameter D2 after release at room temperature. A new set of identical circular tube samples (initial inner diameter D0) was taken, and the sample was radially expanded by 4.5 times and fitted with the mandrel. The sample with the mandrel in the expanded state was placed in a hot air circulating oven preheated to 100℃ and aged continuously for 72 hours. After aging, the sample was removed and cooled at 25℃ for 4 hours with the mandrel attached. The sample was then quickly released from the mandrel and allowed to spring back freely at room temperature for 5 minutes. The inner diameter D3 after aging and release was measured. According to the GB / T 7759.1-2015 standard, the deformation compression was 25%. , The test results are shown in Table 2.
[0092] Table 2 Mechanical strength only constitutes the physical shell of the cold-shrink accessories. The material must have extremely low aging deformation loss after stretching and expansion, otherwise the accessories will loosen. The aforementioned process scheme specifically adds a high-temperature circulating hot air secondary vulcanization process lasting up to 4 hours, aiming to deeply eliminate residual stress, eliminate by-products, and improve the cross-linking network. In Examples 1, 4, and 5, the permanent deformation rate was successfully locked below 10% after both room temperature and 100°C heat aging. This indicates that with the optimization of the co-vulcanization modification amount of the core-shell composite particles, the high-density three-dimensional cross-linking network and strong interfacial anchoring points are tightly interwoven. Even after the polymer chains are stretched by an ultra-high ratio of 4.5 times, the cross-linking network can still effectively resist the sliding shear and viscous rheology between the macromolecular chains.
[0093] In Comparative Example 1, the lack of a dopamine interlayer resulted in numerous microscopic voids and structural defects at the filler-base rubber interface. Under long-term 4.5 times radial expansion stress and high-temperature aging conditions, these interface defects failed to constrain the conformational relaxation of macromolecular chain segments, easily leading to interfacial debonding and microscopic deformation slippage, resulting in significantly excessive macroscopic shrinkage and permanent deformation. In Comparative Example 3, a severe deficiency of low-molecular-weight hydrogen-containing silicone oil caused an imbalance in the molar ratio of silicon hydrogen to vinyl groups. The vulcanized rubber failed to establish a sufficient chemical cross-linking network density, and the matrix mainly consisted of uncross-linked linear long chain segments. Under 4.5 times high strain stretching, these long chain segments underwent severe irreversible viscous rheological and deentanglement behaviors. After accelerated thermal aging, the elastic recovery force was almost completely lost, and the permanent deformation rate deteriorated precipitously.
[0094] Test Example 3 This test quantitatively evaluates the macroscopic insulation withstand voltage rating and dynamic microscopic polarization loss of special silicone rubber by establishing a standard alternating electric field and a high-voltage discharge field. All circular thin-film samples required for the test are molded, requiring a smooth surface free of bubbles and scratches. Before testing, the sample surface is wiped clean with anhydrous ethanol and dried. The specific test method is as follows.
[0095] The relative permittivity and dielectric loss tangent were determined according to GB / T 1409-2006, "Recommended Methods for Measuring Permittivity and Dielectric Loss Factor of Electrical Insulating Materials at Power Frequency, Audio Frequency and High Frequency". A circular specimen with a diameter of 50 mm and a thickness of 1.0 mm was used for dielectric performance testing. The specimen was placed between the center electrode and the annular protective electrode of a standard three-electrode clamp, and a constant clamping force was applied. The reference frequency of the high-precision LCR meter was set to 1 kHz, and an effective AC voltage of 1.0 V was applied. The capacitance value Cx and the dielectric loss tangent tanδ were read at an ambient temperature of 23℃. Finally, the relative permittivity εr was calculated based on the geometric contact area A and the actual thickness h of the specimen.
[0096] The power frequency breakdown strength was determined according to GB / T 1408.1-2016 "Electrical Strength Test Methods for Insulating Materials Part 1: Tests at Power Frequency". A circular specimen with a diameter of 100 mm and a thickness of 1.0 mm was used for the power frequency breakdown test. The specimen, with a thickness of h, was flatly sandwiched between symmetrical cylindrical electrodes and vertically immersed in an oil tank filled with 25# transformer oil to prevent surface flashover. A high-voltage detection source was activated, using a continuous uniform voltage increase method at a rate of 1.0 kV / s, continuously increasing the voltage until the specimen experienced instantaneous electrical breakdown. The effective voltage value at the moment of breakdown was recorded. Five parallel specimens were repeated for each test group, and the average value was taken as the power frequency breakdown strength value for that group. The final test results for each embodiment and comparative example are summarized in Table 3.
[0097] Table 3 In the operating environment of high-voltage cable terminals, accessories must undertake the core functions of dispersing electric field stress concentration at the electrical insulation terminal and preventing insulation breakdown. The polarization behavior and charge migration of the dielectric are highly dependent on the interfacial state of the filler in the silicone rubber matrix and the integrity of the cross-linked network. With the increase of high-dielectric titanium dioxide shell doping, the relative permittivity is steadily adjustable, and the power frequency breakdown strength is maintained above 31kV / mm. Due to the complete and uniform surface modification of the core and shell particles and the moderate depth of the interfacial charge trap, the dielectric loss tangent is firmly limited to below 0.005.
[0098] Comparative Example 2 lacked high-speed, high-pressure shearing and rapid mold opening and closing for venting during injection molding, resulting in residual trace gases and micropore defects inside the rubber compound. Under a power frequency high-voltage alternating electric field, sudden changes in the dielectric within the pores easily triggered partial discharge. Simultaneously, the disordered distribution of fillers caused local electric field distortion, leading to an increase in the dielectric loss tangent and a significant decrease in power frequency breakdown strength. Comparative Example 4 omitted high-temperature secondary vulcanization, resulting in a low crosslinking density and the presence of numerous unreacted small molecule byproducts and free polar groups. Under a 1kHz alternating electric field, the unanchored free groups oscillated violently with the electric field, causing severe reorientation polarization loss. Furthermore, the loose network structure amplified the migration rate of impurity ions under a strong electric field, making internal partial discharge highly susceptible to electron avalanche channels, leading to a sharp degradation in power frequency breakdown strength.
[0099] Test Example 4 This test quantitatively measures the long-term clamping pressure and mechanical engagement resistance against axial slippage by simulating the actual microscopic interface of the contact between cold-shrink accessories and the main insulation of cross-linked polyethylene (XLPE) cables. Simulated mandrel: A standard solid mandrel with an outer diameter of Dl and a constant surface roughness is machined from high-voltage cable XLPE insulation material. A circular tube with an inner diameter of D0 and a length of 100mm is cut, ensuring that Dl is 3.0-4.0×D0. A miniature flexible thin-film pressure sensor with a pressure measurement range of 0-500kPa and a multi-channel data acquisition instrument are also used.
[0100] For the interface pressure test of the main insulation of the cable, a flexible thin film pressure sensor is attached to the outer surface of the XLPE mandrel. Then, the cold shrink tube sample is radially expanded and tightened on top of the sensor. It is left to stand at 25°C for 24 hours to reach equilibrium. The normal static pressure after stabilization is directly read and recorded by a data acquisition instrument.
[0101] The interfacial interlocking force test involved mounting the statically balanced components onto a material testing machine. An XLPE mandrel was fixed to the base, and a clamp on the testing machine was used to secure the outer wall of the cold shrink tubing in a ring. An axial pull-out speed of 50 mm / min was set for tensile testing. The maximum axial pull-out force load during the axial sliding of the cold shrink tubing along the mandrel was recorded, which is the interfacial interlocking force. The test results are shown in Table 4.
[0102] Table 4 The material needs to provide a durable interfacial mechanical response while ensuring hardness. The interfacial pressure and interlocking force between the cold-shrink accessories and the main cable insulation (XLPE) directly determine whether the terminal will experience axial slippage and whether trace amounts of moisture will infiltrate during high-voltage operation. Table 4 shows that as the total content of fumed silica and core-shell composite particles gradually increases, the high-rigidity filler network and co-vulcanization chemical crosslinking points are superimposed by the preparation method, resulting in a simultaneous improvement in the macroscopic stiffness and resilience of the material. This allows the silicone rubber to generate and maintain good continuous interfacial pressure after being fitted with a standard mandrel. At the same time, the high-density chemical network increases its microscopic frictional resistance with the XLPE surface, resulting in excellent interfacial interlocking force.
[0103] The reduction in hydrogen-containing silicone oil in Comparative Example 3 resulted in an incomplete hydrosilylation reaction, with the vulcanized rubber almost resembling a semi-vulcanized gel. Due to the lack of chemical deformation recovery force from the three-dimensional cross-linked network, irreversible viscous slippage and deentanglement occurred between the molecular chains. The principle of the precipitous drop in interfacial pressure: After the mandrel is inserted, the relaxed network cannot convert the expansion deformation into a continuous elastic contraction force, and the internal stress of the material rapidly undergoes physical relaxation, which macroscopically manifests as a decrease in interfacial pressure, making it unable to prevent the intrusion of external moisture. The decrease in interfacial interlocking force is due to the lack of chemical bond traction among the uncross-linked long chains. When pulled out by external force, they not only fail to provide rigid resistance, but the free low-molecular-weight substances on their surface act as a reverse lubricant in linear slippage, leading to a sharp drop in the micro-friction coefficient. The axial pull-out resistance interfacial interlocking force is only 68N, which makes it extremely easy for accessory terminal displacement and slippage accidents to occur in actual operation.
Claims
1. A special silicone rubber for cold-shrink cable termination accessories, characterized in that, The raw materials for its preparation include 1000 parts of special polymethyl vinyl siloxane, 220-280 parts of fumed silica, 410-490 parts of core-shell composite particles, 50 parts of hydroxyl silicone oil, 35-75 parts of polydimethylsiloxane, and 17-25 parts of low molecular weight hydrogen-containing silicone oil. The core-shell composite particles are prepared by hydrothermally growing a titanium dioxide shell on the surface of inorganic nanonuclei after modification with dopamine hydrochloride, and then modifying it with γ-methacryloyloxysilane coupling agent by reflux. The special polymethyl vinyl siloxane adhesive is prepared by stepwise chain extension polymerization and reduced pressure monomer removal process of organosilicon cyclic monomers and vinyl cyclic monomers under the action of silanol catalyst.
2. The special silicone rubber for cold-shrink cable terminations according to claim 1, characterized in that, The preparation method of the core-shell composite particles is as follows: fumed silica is added to deionized water for high-shear dispersion, the system is adjusted to alkalinity using an alkaline solution, dopamine hydrochloride is added and stirred at room temperature for reaction; after centrifugation and washing, the particles are redispersed in an alcohol-water mixed solvent, and tetrabutyl titanate is added dropwise for hydrothermal reaction; finally, γ-methacryloyloxypropyltrimethoxysilane is added for reflux modification, and the particles are obtained by filtration, vacuum drying and grinding.
3. The special silicone rubber for cold-shrink cable terminations according to claim 2, characterized in that, In the preparation method of the core-shell composite particles, tetrabutyl titanate is added at a rate of 1.5-2.5 mL / min, and the temperature is raised to 75℃-78℃ for hydrothermal reaction for 10-12 h; 2% of the total mass of the γ-methacryloyloxypropyltrimethoxysilane is added, and the mixture is refluxed at 60℃ for 2.5-3.5 h for modification.
4. A method for preparing the special silicone rubber for cold-shrink cable termination accessories as described in claim 1, characterized in that, The preparation method is as follows: S1 Mixing: Special polymethyl vinyl siloxane rubber is preheated in a mixer, followed by the sequential addition of fumed silica, core-shell composite particles, and hydroxyl silicone oil. The mixer is started and heated, and maintained under vacuum. After the material cools, polydimethylsiloxane and a vulcanization inhibitor are added, and the mixture is passed through a two-roll mill. Finally, low-molecular-weight hydrogen-containing silicone oil and a platinum complex catalyst are added, and the mixture is stirred until homogeneous before being sheeted. S2 injection molding: The rubber material is injected into the mold cavity with logarithmic spiral micro-guide grooves on the inner wall of the mold. The injection process adopts three-stage speed and pressure control: filling stage, compaction stage and holding pressure stage, and is coordinated with mold opening and closing for venting. S3 vulcanization and post-treatment: The mold is heated and vulcanized at a constant temperature for in-mold molding. After demolding, the part is put into the mandrel and placed in the oven for secondary vulcanization. Finally, it is radially stretched by a radial expansion device and a polypropylene spiral support strip is inserted.
5. The method for preparing the special silicone rubber for cold-shrink cable termination accessories according to claim 4, characterized in that, In step S1, 1000 parts of the special polymethylvinylsiloxane adhesive are preheated to 58℃-62℃, and 240-260 parts of fumed silica, 420-480 parts of core-shell composite particles, and 50 parts of hydroxyl silicone oil are added sequentially. The temperature is then raised to 158℃-162℃ and maintained at a vacuum of -0.094MPa to -0.096MPa for 180 minutes. After the material is cooled to 40℃, 45-55 parts of polydimethylsiloxane and 0.25-0.35 parts of the vulcanization inhibitor 1-ethynyl-1-cyclohexanol are added. The mixture is passed through a thin stream 5 times. Finally, 18-22 parts of low-molecular-weight hydrogen-containing silicone oil with an active hydrogen mass fraction of 1.0% and 0.1 parts of platinum complex catalyst are added.
6. The method for preparing the special silicone rubber for cold-shrink cable terminations according to claim 4, characterized in that, The inner wall of mold S2 is pre-fabricated with logarithmic spiral micro-guide grooves with a depth of 0.18-0.22mm and a pitch of 4.5-5.5mm; the rubber compound is in a 42-48cm... 3 The initial flow rate is injected into the mold at 38-42 mm / s. In the filling stage, the material is injected at a speed of 38-42 mm / s, and the injection pressure is set to 155-165 bar. In the compaction stage, the speed is reduced to 8-12 mm / s, and the injection pressure is maintained at 135-145 bar. In the holding stage, the material is injected at a speed of 8-12 mm / s and the pressure is set to 75-85 bar. The mold is opened and closed 2-4 times to release air.
7. The method for preparing the special silicone rubber for cold-shrink cable terminations according to claim 4, characterized in that, In S3, the mold is heated to 168℃-172℃ and vulcanized at a constant temperature for 7.5-8.5 minutes. After demolding, the parts are placed in an oven with a hot air circulation rate of 1.8 m / s and heated to 195℃-205℃ at a rate of 1.8℃-2.2℃ / min for secondary vulcanization for 3.5-4.5 hours. Finally, the finished product is radially stretched.